2021
DOI: 10.3390/cancers13061434
|View full text |Cite
|
Sign up to set email alerts
|

A Cystine-Cysteine Intercellular Shuttle Prevents Ferroptosis in xCTKO Pancreatic Ductal Adenocarcinoma Cells

Abstract: In our previous study, we showed that a cystine transporter (xCT) plays a pivotal role in ferroptosis of pancreatic ductal adenocarcinoma (PDAC) cells in vitro. However, in vivo xCTKO cells grew normally indicating that a mechanism exists to drastically suppress the ferroptotic phenotype. We hypothesized that plasma and neighboring cells within the tumor mass provide a source of cysteine to confer full ferroptosis resistance to xCTKO PDAC cells. To evaluate this hypothesis, we (co-) cultured xCTKO PDAC cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…This could be attributed to the lower oxidative pressure that cells experience in these conditions. However, another possibility that became apparent in our previous work with xCT-KO xenografts is cell-to-cell interplay which, in the case of xCT-KO cells, provides them with the source of reduced cysteine [28,38]. Although the degradation of GSH in vivo is just as intensive as in vitro [35,[39][40][41], the continuous flux of GSH from adjacent cells might be a sufficient source of GSH for GCLc-KO cells to survive and thrive in vivo.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This could be attributed to the lower oxidative pressure that cells experience in these conditions. However, another possibility that became apparent in our previous work with xCT-KO xenografts is cell-to-cell interplay which, in the case of xCT-KO cells, provides them with the source of reduced cysteine [28,38]. Although the degradation of GSH in vivo is just as intensive as in vitro [35,[39][40][41], the continuous flux of GSH from adjacent cells might be a sufficient source of GSH for GCLc-KO cells to survive and thrive in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…Based on our previous experience with xCT-KO cell growth in vivo, a potential explanation for GCLc-KO tumor cell survival and proliferation in the same conditions could be attributed to GSH exchange between GCLc-KO and the neighboring WT cells in the tumor mass. To investigate this issue, we used co-culture (cc) of Capan-2 or MiaPaCa-2 GCLc-KO cells and LS174T WT cells (cell line chosen based on the results from our previous study [28]). LS174T cells were pre-seeded in the upper well of a Boyden chamber 24 h before GCLc-KO cells, and the viability of the latter was investigated 96 h later (Figure 6C).…”
Section: Gclc Is Dispensable For Pdac Cell Growth In Vivomentioning
confidence: 99%
“…However, in vivo SLC7A11 knock out PDAC cells grew normally. Their further study showed that the presence of a cysteine/cystine shuttle between neighboring cells is the mechanism that provides redox and nutrient balance, and thus ferroptotic resistance in SLC7A11 knock out PDAC cells ( Meira et al, 2021 ). Cysteine is required for preventing ferroptosis in pancreatic cancer (2020a), While the raw material for the synthesis of cysteine is mainly provided by System X c − .…”
Section: Potential Roles Of Targeting System X C ...mentioning
confidence: 99%
“…Dr Vucetic explained that xCT plays its fundamental role in cyst(e)ine import exclusively or almost exclusively in an oxidised form ( in vitro conditions), and that in vivo , cysteine‐reduced form can come from different sources. Interestingly, this work demonstrated that neighbouring fibroblasts secrete small ‘rescue agents’ for the xCT‐KO tumours allowing the complete prevention of ferroptosis [6].…”
Section: Session I: Redox and Energy Metabolismmentioning
confidence: 99%